Optimalisasi Peran Audit Internal dan Pengendalian Internal dalam Pencegahan Fraud di Sektor Publik Indonesia: Studi Komparatif dan Pengembangan Model - Dito Aditia Darma Nst; Tri Hayati; Raihatunnisa Bangun; Muhammad Arsyad Hawari Muchsin; Glen Hasian Marpaung (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze and optimize the role of internal audit and internal control in preventing fraud within Indonesia’s public sector. Given the prevalence and detrimental impact of fraudulent activities in governmental environments, this study adopts a mixed-methods approach, combining an in-depth synthesis of the literature with a comparative analysis of practices and frameworks across various public sector organizations. Through a literature review and comparative study, this research identifies key factors influencing the effectiveness of both functions and develops a more comprehensive fraud prevention model. The findings indicate that the optimization and strategic synergy between internal audit and internal control strengthened by continuous improvement of auditor competencies, proactive utilization of data analytics technology, the cultivation of an organizational culture emphasizing transparency and accountability, and inter-agency collaboration can substantially reduce vulnerability to fraud and enhance sound financial governance across the public sector. The proposed fraud prevention model integrates key components, including the strengthening of the control environment, enhanced risk assessment, effective implementation of control activities, reinforcement of information and communication systems, and improved monitoring mechanisms.